2020
DOI: 10.1038/s41598-020-78002-0
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a transmucosal sublingual fentanyl tablet as a procedural pain treatment in colonoscopy patients: a prospective placebo-controlled randomized study

Abstract: Since patients often experience pain and unpleasantness during a colonoscopy, the present study aimed to evaluate the efficacy and safety of sublingually administered fentanyl tablets for pain treatment. Furthermore, since the use of intravenous drugs significantly increases colonoscopy costs, sublingual tablets could be a cost-effective alternative to intravenous sedation. We conducted a prospective placebo-controlled randomized study of 158 patients to evaluate the analgesic effect of a 100 µg dose of sublin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The intravenous route is the most effective way to administer benzodiazepines; however, it needs close patient monitoring, complete equipment, and expert nurses to deal with probable side effects. 20 Oral and sublingual administration are alternative routes and possibly will be a cost-effective method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intravenous route is the most effective way to administer benzodiazepines; however, it needs close patient monitoring, complete equipment, and expert nurses to deal with probable side effects. 20 Oral and sublingual administration are alternative routes and possibly will be a cost-effective method.…”
Section: Discussionmentioning
confidence: 99%
“…The intravenous route is the most effective way to administer benzodiazepines; however, it needs close patient monitoring, complete equipment, and expert nurses to deal with probable side effects. 20 Oral and sublingual administration are alternative routes and possibly will be a cost-effective method. Previous investigations have revealed that these routes can decrease anxiety and discomfort related to the operation and upsurge the tolerance and satisfaction of the patients.…”
Section: Discussionmentioning
confidence: 99%